ITEM ANALYSIS AND PEER-REVIEW EVALUATION OF SPECIFIC HEALTH PROBLEMS AND APPLIED RESEARCH BLOCK EXAMINATION - Novi Maulina; Rima Novirianthy (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2020)
Background: Assessment and evaluation for students is an essential component of teaching and learning process. Item analysis is the technique of collecting, summarizing, and using students’ response data to assess the quality of the Multiple Choice Question (MCQ) test by measuring indices of difficulty and discrimination, also distracter efficiency. Peer review practices improve quality of assessment validity in evaluating student performance.Method: We analyzed 150 student’s responses for 100 MCQs in Block Examination for its difficulty index (p), discrimination index (D) and distractor efficiency (DE) using Microsoft excel formula. The Correlation of p and D was analyzed using Spearman correlation test by SPSS 23.0. The result was analyzed to evaluate the peer-review strategy.Results: The median of difficulty index (p) was 54% or within the range of excellent level (p 40-60%) and the mean of discrimination index (D) was 0.24 which is reasonably good. There were 7 items with excellent p (40–60%) and excellent D (≥0.4). Nineteen of items had excellent discrimination index (D≥0.4). However,there were 9 items with negative discrimination index and 30 items with poor discrimination index, which should be fully revised. Forty-two of items had 4 functioning distracters (DE 0%) which suggested the teacher to be more precise and carefully creating the distracters.Conclusion: Based on item analysis, there were items to be fully revised. For better test quality, feedback and suggestions for the item writer should also be performed as a part of peer-review process on the basis of item analysis.